Mediation and its applications for good decision making and dispute resolution / Carrie Menkel-Meadow. - Menkel-Meadow, Carrie (Acta Falconis (Intersentia (Firm)), 2016)
In this book, the author argues that mediation is one of the basic human building blocks of a process that allows us to truly hear from each other in the hope that we can resolve our conflicts, explore our differences, as well as complementarities, find mutual understanding, and achieve better outcomes and solutions to legal, social and political problems. Such an effort to "reorient the parties to a dispute to each other," and to facilitate the solving of problems and, in the best of all worlds, the making of peace, requires an interdisciplinary orientation in which human knowledge and understandings drawn from a variety of constituent fields - older ones like history, law, psychology, sociology, economics, political science and international relations, and newer ones, including decision sciences, game theory and urban planning.